Հերետիկոսութիւնից Ընդհանրական եկեղեցի դարձի եկածների ընդունման կարգը եւ դրա արտացոլումը Մխիթար Վարդապետ Գոշի «Թուղթ առ վրացիսն՝ Յաղագս ուղղափառութեան հաւատոյ» երկում - Մկրտչեան, Վաչէ Աբղյ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Данная статья исследует историческое развитие и богословские основы порядка принятия обращённых из еретических общин в лоно Вселенской (Кафолической) Церкви, с особым акцентом на отражение этой практики в каноническом сочинении Мхитара Гоша — «Послание к грузинам». Автор подробно рассматривает различные способы приема в Церковь: через Крещение, Миропомазание или покаяние — в зависимости от того, был ли человек ранее крещён в еретической общине, и насколько та была удалена от православия. В работе анализируются труды св. Киприана Карфагенского, св. Василия Великого, решения Никейского и Константинопольского соборов, а также Трулльского собора. Особое внимание уделено армянской церковной традиции, в частности позиции Мхитара Гоша в его «Послании к грузинам», написанном на фоне напряжённых отношений между Армянской и Грузинской церквами в XII—XIII вв. Гош резко осуждает практику взаимного перекрещивания, считая её противной канонам, и предлагает тройную схему приёма: крещением, миропомазанием или через покаяние. Он опирается как на армянскую, так и на византийскую каноническую традицию (включая источники, отсутствующие в армянских сборниках), чтобы доказать недопустимость перекрещивания армян со стороны грузин. Статья подчёркивает, что труд Гоша отражает не только полемическую защиту армянской церковной идентичности, но и свидетельствует о восприятии общецерковных принципов приёма еретиков, что подчёркивает согласие Армянской Церкви с широкой христианской традицией. This article examines the historical development and theological foundations of the procedure for accepting converts from heretical communities into the bosom of the Universal (Catholic) Church, with a particular focus on how this practice is reflected in Mkhitar Gosh’s canonical work, “Letter to the Georgians.” The article traces the early Church’s approaches to the reintegration of heretics - distinguishing between those originally baptized in the Church who later deviated, and those who were baptized outside the Church. It outlines different practices (rebaptism, chrismation, or penitential reception) as they evolved in East and West, drawing on key sources such as St. Cyprian of Carthage, St. Basil the Great, and the decisions of the Councils of Nicaea and Constantinople, as well as the Council of Trullo. Particular attention is paid to the historical response of the Armenian Church tradition, in particular expressed by Mkhitar Gosh in his “Letter to the Georgians,” written against the backdrop of tense relations between the Armenian and Georgian Churches in the 12th-13th centuries. Gosh sharply condemns the practice of mutual rebaptism as canonically unlawful, and proposes a threefold model of reception: through Baptism, Chrismation, or Penance, depending on the nature and origin of the convert’s previous affiliation. Gosh uses patristic and canonical sources (including sources not found in Armenian collections) to refute the Chalcedonian practice of rebaptizing Armenians and to affirm the legitimacy of Armenian sacraments. The study concludes that Gosh’s letter reflects not only a theological refutation of external accusations, but also an internalization of the universal Church principles regarding the return of heretics, thereby strengthening the Armenian Church’s alignment with the broader Christian tradition.
Keywords: Կրօնագիտական; Հայ Եկեղեցի